A good patient? How notions of 'a good patient' affect patient-nurse relationships and ART adherence in Zimbabwe. Issue 1 (December 2015) - Campbell, Catherine; Scott, Kerry; Skovdal, Morten; Madanhire, Claudius; Nyamukapa, Constance; Gregson, Simon
Abstract Background While patient-provider interactions are commonly understood as mutually constructed relationships, the role of patient behaviour, participation in interactions, and characteristics, particularly ideals surrounding notions of 'good' and 'bad' patients, are under-examined. This article examines social representations of 'a good patient' and how these representations affect patient-healthcare provider relationships and antiretroviral treatment (ART) for people living with HIV. Methods Using thematic network analysis, we examined interview and focus group transcripts involving 25 healthcare staff, 48 ART users, and 31 carers of HIV positive children, as well as field notes from over 100 h of ethnographic observation at health centres in rural Zimbabwe. Results Characteristics of a good patient include obedience, patience, politeness, listening, enthusiasm for treatment, intelligence, physical cleanliness, honesty, gratitude and lifestyle adaptations (taking pills correctly and coming to the clinic when told). As healthcare workers may decide to punish patients who do not live up the 'good patient persona', many patients seek to perform within the confines of the 'good patient persona' to access good care and ensure continued access to ART. Discussion The notion of a 'good ART patient' can have positive effects on patient health outcomes. It is one of the only arenas of the clinic experience that ART patients can influence in their favour. However, for people not conforming to the norms of the 'good patient persona', the productive and health-enabling patient-nurse relationship may break down and be detrimental to the patient. Conclusion We conclude that policy makers need to take heed of the social representations that govern patient-nurse relationships and their role in facilitating or undermining ART adherence.